MIR337-3p Enhances Mycobacterial Pathogenicity Involving TLR4/MYD88 and STAT3 Signals, Impairing VDR Antimicrobial Response and Fast-Acting Immunity - Liang, Shanshan; Huang, Guixian; Wu, Tian; Peng, Ying; Liu, Xi; Ji, Xuejiao; Sha, Wei; Wang, Feifei; Shen, Ling; Shen, Hongbo (Frontiers in Immunology, 2021)
Active form of Vitamin D (VitD) enhances human innate immunity against Mycobacterium tuberculosis (Mtb) infection. Our previous work found that miR-337-3p was highly expressed in T cells of TB patients. Here, we identified the mechanism of miR-337-3p in regulation of fast-acting anti-TB immunity by inhibiting Vitamin D receptor (VDR) antimicrobial response. While high-level miRNA-337-3p expression was induced by mycobacterial infection in cellular models and mice, TB patients exhibited significantly-increased miR-337-3p in CD14+ monocytes/macrophages, innate-like Vγ2+ T cells, and CD8+lymphocytes containing NK/innate lymphoid cells. miR-337-3p promoted the mycobacterial entry/infection and replication/growth in host target cells: macrophages and lung epithelial cells. Such miR-337-3p-enhanced pathogenicity coincided with the miR-337-3p depression of VDR antimicrobial response of CYP27B1/DEFB4A/CAMP pathways. Surprisingly, single miR-337-3p species could specifically target both the Tlr4 and Stat3 3’-UTRs (untranslated region) to depress the TLR4/MyD88 and STAT3 signals, and impairing either of the two signals inhibited the VDR antimicrobial pathways in macrophages. miR-337-3p also depressed the Vitamin-D-activated autophagy. Concurrently, human PBMC expressing high-level miR-337-3p exhibited a reduced ability of innate cell populations to mount fast-acting cellular immunity against intracellular mycobacterial infection. Furthermore, a higher expression of miR-337-3p after mycobacterial infection of mice coincided with much greater CFU counts in lungs and even the death of infected animals, whereas miR-337-3p inhibitor treatment of infected mice reduced miR-337-3p levels and reversed miR-337-3p-mediated increases in CFU counts. Thus, TB-driven single miR-337-3p species could specifically target/impair both TLR4/MyD88 and STAT3 activation signals, inhibiting VDR antimicrobial response and fast-acting anti-TB immunity, leading to enhanced pathogenicity.